2004
DOI: 10.1243/0957650041761883
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the performance envelope of combined Rankine, Brayton and two parallel inverse Brayton cycles

Abstract: The study presented in this paper investigated the performance of a proposed system constructed from Brayton, two parallel inverse Brayton and Rankine cycles. It has been carried out by varying the Brayton cycle pressure ratio for different values of expansion pressures of the two inverse Brayton cycles using variable inlet pressures, above atmospheric. The results revealed that the best theoretical performance could be achieved when the system was simulated with a high value of expansion pressure of the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
1
13
1
Order By: Relevance
“…Alabdoadaim et al [10] investigated a combined Rankine, Brayton and two parallel inverted Brayton cycles, and found that the system had a maximum thermal efficiency of 54%, achieved by altering the expansion ratio of the second inverted Brayton cycle. Alabdoadaim et al [11] studied a combined Rankine, Brayton and inverse Brayton cycle and attained a maximum thermal efficiency of 57.7%.…”
Section: Figure 1: Inverted Brayton Cyclementioning
confidence: 99%
“…Alabdoadaim et al [10] investigated a combined Rankine, Brayton and two parallel inverted Brayton cycles, and found that the system had a maximum thermal efficiency of 54%, achieved by altering the expansion ratio of the second inverted Brayton cycle. Alabdoadaim et al [11] studied a combined Rankine, Brayton and inverse Brayton cycle and attained a maximum thermal efficiency of 57.7%.…”
Section: Figure 1: Inverted Brayton Cyclementioning
confidence: 99%
“…The study of combined Brayton/Rankine cycle with the use of regenerators has been a point of focus for some researchers. Bejan et al (2012) showed that the path to improve the efficiency of regenerator, aiming the maximum heat transfer and minimum head loss, was to turn the current parallel channel Engenharia Térmica (Thermal Engineering), Vol. 16 • No.…”
Section: Introductionmentioning
confidence: 99%
“…In order to do that, it would be necessary to make appropriate use of the existing technologies, without the need of waiting for new technological development of turbines. Alabdoadaim et al (2004) investigated the performance of a big cycle composed of a Brayton, two reverse parallel Brayton and a Rankine cycle. The expansion pressure relation between the two reverse Brayton cycles was varied, considering values above the atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The exergy analysis and optimization of the combined Brayton and inverse Brayton cycles were performed by Zhang et al [39]. Based on the combined Brayton and inverse Brayton cycles, Alabdoadaim et al [40][41][42] proposed its developed configurations including regenerative cycle and reheat cycle, and using two parallel inverse Brayton cycles as bottom cycles. They found that the system with regeneration attains higher heat efficiency than that of the base system, but with smaller work output based on the first law analysis.…”
Section: Introductionmentioning
confidence: 99%